Developing Art Market Desain in Medan (With a Neo-vernacular Approach) (International Journal of Architecture and Urbanism, 2021)
Abstract. Medan is a historical and multi-ethnic city which is one of the tourist destinations in Indonesia. Medan has many cultures that produce a lot of arts and crafts from each culture. However, the facilities and infrastructure for culture are still lacking. Only Cultural Park and PRSU are cultural spaces facilitated by the government. From the private sector, several galleries sell creative cultural industries that are managed privately. Therefore, this study aims as a boost where it is necessary to build a centre for a complete arts and crafts shop as a medium for art artisans to explore their talents and to help the economy of the surrounding community. Data collection in this study relies on secondary data obtained from libraries, related offices related to urban planning such as the Medan City Planning Agency and online sources. Then proceed with observing the location of potential sites as art markets. These observations emphasize apart from the location of the site as well as on the environment and infrastructure around the site. The results of the study show that: the right location for designing an art market in Medan is on Palang Merah street. This location is considered suitable because of its strategic location, close to the city centre and close to culinary spots. With this art market, it can become a workshop or marketing place for the creative industry in Medan.